THE ROLE OF LEXICAL VARIANTS IN THE MODERN RUSSIAN LANGUAGE (Bulletin of Innovative Research, 2026)
The article examines the role of lexical variants in the modern Russian language as one of the manifestations of linguistic variability. The main types of lexical variants, the reasons for their emergence, and their functions in the language system are analyzed. Special attention is paid to the influence of social, cultural, and historical factors on the formation of lexical variability. The importance of lexical variants for the development of the Russian vocabulary, ensuring stylistic diversity of speech, and improving communication accuracy is emphasized. It is concluded that lexical variability is a natural and necessary phenomenon in the development of the modern Russian language.